2009
DOI: 10.1007/s11172-009-0216-y
|View full text |Cite
|
Sign up to set email alerts
|

Structures of germylenes and stannylenes with chelating ligands: a DFT study

Abstract: Geometries of 20 germylenes and 18 stannylenes based on dialkanolamines, diethylenetri amines, and related compounds were optimized by the DFT method. It was found that the most of the germylenes and stannylenes studied are more stable as dimeric structures of different types. The dimerization is possible due to either additional Ge-O(N) interactions or Ge-Ge bonding. The factors leading to the stabilzation of one or another isomer are examined.Presently, investigation of compounds containing di valent Group 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Hydrogen atoms are omitted for clarity. DFT calculations have shown that for 2,8dioxa-5-aza-1-stanna(II)bicyclo [3.3.0]octanes of the type RN(CH 2 CH 2 O) 2 Sn (R = H, Me, Ph) the cis isomer is more stable than the trans isomer with energy differences that range from 2.6 (R = H) to 1.3 kcal mol -1 (R = Ph), [6] but no calculations were performed for sterically more crowded stanna(II)bicyclo [3.3.0]octane derivatives. (5) Sn(1)···Sn(X) 3.6353(1) 3.6124 (3) 3.5966 (3) 3.4697 (3) 3.5229 (4) 3.3927 (4) 3.4440 (3) (27) 3.9435 (1) 2.239(9) Å; Sn-N: 2.413(10), 2.447(10) Å].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hydrogen atoms are omitted for clarity. DFT calculations have shown that for 2,8dioxa-5-aza-1-stanna(II)bicyclo [3.3.0]octanes of the type RN(CH 2 CH 2 O) 2 Sn (R = H, Me, Ph) the cis isomer is more stable than the trans isomer with energy differences that range from 2.6 (R = H) to 1.3 kcal mol -1 (R = Ph), [6] but no calculations were performed for sterically more crowded stanna(II)bicyclo [3.3.0]octane derivatives. (5) Sn(1)···Sn(X) 3.6353(1) 3.6124 (3) 3.5966 (3) 3.4697 (3) 3.5229 (4) 3.3927 (4) 3.4440 (3) (27) 3.9435 (1) 2.239(9) Å; Sn-N: 2.413(10), 2.447(10) Å].…”
Section: Resultsmentioning
confidence: 99%
“…In the solid state, 9·0.5C 7 H 8 is a centrosymmetric dimer formed by intermolecular OǞSn interactions to give a fourmembered Sn 2 (7), 176.01 (6), and 148.00(10)°, (2) Sn (1)-O(21) 2.050 (7) Sn(1)-N (14) 2.245 (3) 2.247(6) Sn(1)-Br (1) 2.5601 (5) 2.5158(10) Sn(1)-Br (2) 2.5604 (5) 2.5340 (10) Sn (2)-O(11) 2.081 (5) Sn (2)-O(21) 2.116 (8) Sn (2)-O(27) 2.104 (5) Sn (2)-O(31) 2.091 (5) Sn (2)-Br (3) 2.5032(10) Sn(2)-Br (4) 2.5024(10) Sn(3)-Br (5) 2.5261(10) Sn(3)-Br (6) 2.5306 (10) Sn (3)-O(27) 2.073 (5) Sn (3)-O(31) 2.145 (5) Sn (3)-O(37) 2.018 (5) Sn (3)-N(34) 2.247 (6) Sn (1)···Sn(1A) 3.4080 (4) Sn (1)···Sn (2) 3.3365 (2) Sn (2)···Sn (3) 3.3397 (1) O(27)···O (17) 2.586 (8) O(21)···O (37) 2.609 (8) respectively. The intramolecular Sn (1) [11] The Sn(1)-Br(1) and Sn(1)-Br (2) Compound 10 can formally be interpreted as an insertion product of molecular SnBr 2 (OH) 2 into the intermolecular Sn-O bridge of the dimeric compou...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations